Factors that lead bumiputera to join small medium enterprise (SMEs) in Melaka / Noor Faralyana Azis and Muhammad Nurhazwan Md Tahil - Azis, Noor Faralyana; Md Tahil, Muhammad Nurhazwan (Faculty of Administrative Science and Policy Studies, 2014)
The aim of this quantitative research is to identify the factor that lead bumiputera involve in Small Medium Enterprise (SMEs) in Melaka. There are five variables were used in this research to collect quantitative data from the subjects which were self-employed, job satisfaction, financial reward, environmental factor and level of skill and knowledge. The respondents for this study consist of bumiputera that involve in Small Medium Enterprise (SMEs) in area Melaka. The data from this research was collected by questionnaire that given to the respondents. 70 questionnaires had been design and distribute randomly among entrepreneurs to identify whether there is a relationship between independent variables and dependent variables. Then the data were analysing using reliability analysis, frequency analysis, Pearson’s Rank Correlation Coefficient and multiple linear regressions. Result of the study show that there is significance negative one variable and the rest are positive significance. The result also indicate that level of skill and knowledge was found to be the only independent variable with most significant factor that lead bumiputera involve in SMEs in Melaka (b=0.325, p<0.002).